2019
DOI: 10.1016/j.artd.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Trends in computer navigation and robotic assistance for total knee arthroplasty in the United States: an analysis of patient and hospital factors

Abstract: Background Computer navigation and robotic assistance technologies are used to improve the accuracy of component positioning in total knee arthroplasty (TKA), with the goal of improving function and optimizing implant longevity. The purpose of this study was to analyze trends in the use of technology-assisted TKA, identify factors associated with the use of these technologies, and describe potential drivers of cost. Methods The Nationwide Inpatient Sample database was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
105
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 51 publications
9
105
1
Order By: Relevance
“…Specifically, we found that TA-THA was more likely to be done in the Western region compared to the Northeast region. This finding is similar to what numerous other studies have shown which is that use of technology assistance in arthroplasty surgery, whether it is computer-assisted navigation or robotic assistance, is more prevalent in the Western region of the United States [22,34].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Specifically, we found that TA-THA was more likely to be done in the Western region compared to the Northeast region. This finding is similar to what numerous other studies have shown which is that use of technology assistance in arthroplasty surgery, whether it is computer-assisted navigation or robotic assistance, is more prevalent in the Western region of the United States [22,34].…”
Section: Discussionsupporting
confidence: 90%
“…We found no differences in the likelihood of undergoing TA-THA based on hospital size or type. These findings are similar to what Antonios et al showed in their analysis of TA-TKA but differ from Bohl et al in their retrospective study of THA with computer- assisted navigation [22,34]. Specifically, Bohl et al [22] showed that large, teaching medical centers had increased utilization of computer-assisted navigation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar patterns of savings have been noted in a recent systematic review of robotic assisted technologies. 7 We found no statistically significant differences in reoperations, complications, ED visits, and 30-or 90-day readmissions comparing raTKA and mTKA. Other investigators have reported differences in these outcomes comparing raTKA and mTKA techniques.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous short-term follow-up studies demonstrate that raTKA results in improved postoperative pain, length of stay (LOS), and discharge disposition compared with jig-based mTKA techniques. 4,[7][8][9] The recent introduction of raTKA techniques precludes comparative survivorship analysis with mTKA technique. Other robotic-assisted surgical platforms including unicompartmental knee arthroplasty (raUKA) and total hip arthroplasty (raTHA) have been in clinical use in the United States for over 8 years.…”
mentioning
confidence: 99%